Thinking Critically about Lecturers ' Perceptions and Development of Critical Thinking Skills in Teacher Education Students - Kavenuke, Patrick Severine (Papers in Education and Development, 2021)
Abstract The study was envisaged to examine how lecturers perceive critical thinking skills (CTSs) as well as how they teach to develop such skills in students. The study employed a sample of 42 participants using four data collection methods namely semi-structured interview, focus group discussion, participant observation and artefacts method of data collection. Despite the extant misperceptions of what constitute CTSs among lecturers, findings indicated that lecturers perceive CTSs as skills and abilities, dispositions and skills that enable a person to perform some functions. The study concludes that developing CTSs require changes in the minds of lecturers and students. The study argues that there is no way CTSs could be developed while students are less motivated and unwilling to learn. Keywords: lecturers, perceptions, students, teaching